Researching South African Englishes. Issue 1 (31st March 2020) - Botha, Werner; van Rooy, Bertus; Coetzee‐Van Rooy, Susan
Abstract: In this paper we provide an overview of the current status as well as broad functions of Englishes in South Africa. We also provide a discussion of some of the contemporary concerns related to the complex and multivaried nature of English in the country. This paper further serves to introduce the major themes that are of concern to those researchers that are interested in the study of South African Englishes, through an introduction of the papers that form part of this Special Issue. Finally, we discuss the current state of the art with regards to researching English in the country where we suggest potential future areas of investigation.